Poultry and Fish Intake and Pancreatic Cancer Risk: A Systematic Review and Meta-Analysis. (2nd January 2022) - Gao, Yu; Ma, Yunfei; Yu, Mingwei; Li, Guangda; Chen, Yuhan; Li, Xiaoxiao; Chen, Xinjie; Xie, Ying; Wang, Xiaomin
Abstract: Although several epidemiological studies have investigated associations between poultry and fish consumption and pancreatic cancer (PC) risk, these findings have been inconsistent. The present study aimed to perform a meta-analysis to comprehensively evaluate these associations. We retrieved Eligible cohort studies and case-control studies published before February 2020 from the Medline, EMBASE, and Cochrane Library and applied a random or fixed effects model to calculate the pooled relative risk (RR) and the corresponding 95% confidence intervals (CI). Publication bias was detected using funnel plots, Begg's test, and Egger's test, and the study quality was evaluated using the Newcastle-Ottawa scale. We included 25 studies in the analyses. The pooled RR of PC for the highest vs. lowest poultry intake category was 1.14 (95% CI: 1.02–1.26) in cohort studies. There was no appreciable link between fish intake and PC risk (RR: 1.00, 95% CI: 0.93–1.07). Our results suggest that large amount of poultry intake may increase PC risk, while fish intake is unlikely to be linked to PC risk. These links require further investigation, particularly between poultry and PC.